2010
DOI: 10.1021/jf101893v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disulfide Interactions and Hydrolysis on the Thermal Aggregation of β-Lactoglobulin

Abstract: The roles of sulfhydryl/disulfide interactions and acid/pepsin hydrolysis on β-lactoglobulin (β-lg) thermal aggregation at acidic pH 3.35 and 2 were studied using rheology, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), transmission electron microscopy (TEM), and Western blotting. Pepsin promoted additional hydrolysis compared to the acid-hydrolyzed control sample based on a 12% increase in free amino groups. Hydrolysis with pepsin also resulted in an increase in the apparent viscosity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
6
19
0
2
Order By: Relevance
“…pH 3.5 and 4.0) no fibrils are formed. Acid hydrolysis plays an important role in fibril formation (Akkermans et al, 2008a,b) and was reported to be limited at pH 3.35 compared to pH 2.0 (Mudgal et al, 2011). Moreover, at pH > 3.0 proteins are less charged and thus electrostatic repulsion is much lower than at pH 2.0.…”
Section: Fibril Formation At Different Ph Valuesmentioning
confidence: 96%
“…pH 3.5 and 4.0) no fibrils are formed. Acid hydrolysis plays an important role in fibril formation (Akkermans et al, 2008a,b) and was reported to be limited at pH 3.35 compared to pH 2.0 (Mudgal et al, 2011). Moreover, at pH > 3.0 proteins are less charged and thus electrostatic repulsion is much lower than at pH 2.0.…”
Section: Fibril Formation At Different Ph Valuesmentioning
confidence: 96%
“…1). Heat treatment leads to b-Lg denaturation and the formation of aggregates via thiol-disulphide exchange and also by thiol oxidation and non-covalent interaction aggregation (Mudgal et al, 2011), which can result in unavailable Lys and Gln residues, hampering the formation of crosslinks. On the other hand, the addition of Cys can result in some important changes in the protein structure by disrupting the disulfide bonds (Cys66eCys160 and Cys106eCys109), that connect the C-D loop to the carboxyl-terminal region and strands G and H, opening up the protein globule (Báez, Moro, Ballerini, Busti, & Delorenzi, 2011;Papiz et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…All the samples showed bands with MM < 14.4 kDa, possibly polypeptides formed during the protein preparation(Bateman, Ye, & Singh, 2010;Mudgal, Daubert, Clare, & Foegeding, 2011). The b-Lg…”
mentioning
confidence: 99%
“…Fibrils formation may involve covalent linkages (disulfide bridges) in addition to non-covalent interactions depending on pH. Heat treatment at pH 3.35 assembled fibrils not only by hydrogen bonds and hydrophobic interactions but also by limited number of disulfide bridges; whilst, by heating at pH 2.0 merely non-covalent hydrophobic interactions contributed in fibrils formation (Mudgal, Daubert, Clare, & Foegeding, 2010).…”
Section: Introductionmentioning
confidence: 99%